Johnson & Johnson equity report –J&J fundamentally underappreciated - Branco, Tomás De Andrade Guerra Fazenda (2021)
This report was prepared by Gonçalo André and Tomás Branco, two Master in Finance students of Nova School of Business and Economics (“Nova SBE”), within the context of the Field Lab –Equity Research. The goal was to evaluate Johnson & Johnson’s intrinsic value. Therefore, a thorough analysis of itsoperating segments and industries was conducted. Our valuation model resulted in a share price of $166.00, which led to the conclusion that J&J is trading below its fair value. In addition, it was measured how sensitive the model is to changes in its underlying assumptions and to J&J’s future operating results.